Identification of Allergens by Skin Prick Test in Patients of Pokhara Suffering from Allergic Rhinitis - Acharya, A; Nepali, R; Sigdel, B; Bania, P (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.1 Issue 1 (Jan-Jun 2011) 12-13 DOI: http://dx.doi.org/10.3126/njenthns.v2i1.6777